Analyzing the mobile content consumption in different social contexts: the cases of graduate student usages in Taiwan and U.S.A. - Kuo-feng Tseng (International Telecommunications Society (ITS), 2012)
Could mobile phones become mass media, like television, radio, newspaper or Internet, which provide us information and entertainment? Although the penetration rates of mobile phones are very high in most countries, many users are not willing to spend money on the consumption of mobile online services. To explore those factors, this research analyzed 24 graduate students in different social contexts from Taiwan and the U.S. The results showed that the school life style, WiFi on campus, high mobile service fees, low incomes and low usage utilities made students not willing to spend money on the mobile contents. Instead, the notebooks are the homework and mass media center for most students, and they get those information and entertainment contents from the alternative Internet for free.
Keywords: 330; mobile phone; context; activity theory; business model